Small-scale manufacture of cheese from cow's milk - O'Mahony, F.; Bekele, E. (1985)
Discusses procedures, equipment requirements and yield expectations of two simple methods of making Queso Blanco or Halloumi cheese from cows' milk suitable for a small scale operation.